Lake effect on summer cooling of shorelines and adjacent inland forests on Lake Superior's north shore - Hillman, Ashley; Nielsen, Scott (Zenodo, 2023)
Climate refugia, or areas that are projected to remain relatively stable under climate change, can serve as remnant habitat or steeping stones for species dispersal. The largest freshwater lake in the world by surface area, Lake Superior, serves as a model system for understanding cooling-mediated local refugia, as its cool summer water temperatures and wave action have maintained shoreline habitats suitable for disjunct opulations for arctic-alpine plants since deglaciation. It is known to affect local climates by providing a summer cooling effect near its shorelines, however, the inland gradient of change and spatial patterns of cooling has not been quantified. Here, we describe the extent of the inland cooling gradient, the degree of temperature buffering, and patterns of cooling for Lake Superior's north shore over a 3-year period. Specifically, we established 7 transects along Lake Superior's north shore, with temperature data loggers placed at 10 m, 100 m, 1 km, 10 km, and 100 km inland. We analyzed temperature data by year, month, summer maximum, and growing degree days (GDD 0 ) for each site. Summertime cooling at shore sites (10m) was ~5 °C cooler than inland control sites (100 km), while sites 10 km from the shore were still 1.6 °C cooler than control sites. Magnitude of cooling varied geographically, with sites further west and southeast showing little to no cooling effect. Site on the exposed north and northeast shore where disjunct arctic-alpine plants are most common showed the highest degree of temperature buffering. We also found that shoreline sites on the north and northeast shore had shorter growing seasons compared to inland control sites. Finally, the number of days per year warmer than 16 °C, a maximum temperature threshold associated with arctic-alpine plant occurrences, averaged 65 days per year at 10 m sites and 82 days per year at control sites. The north shore of Lake Superior serves as a transition zone between temperate deciduous forests and boreal forests and is predicted to ...